Hidden intercourse : eros and sexuality in the history of Western esotericism - Hanegraaff, Wouter J.; Kripal, Jeffrey J. 1962- (Aries Book Series, 2008)
From rumours about gnostic orgies in antiquity to the explicit erotic symbolism of alchemical texts, from the subtly coded eroticism of medieval kabbalah to the sexual magic practiced by contemporary occultists and countercultural translations of Asian Tantra, the history of Western esotericism is rich in references to the domains of eros and sexuality. This volume, which brings together an impressive array of top-level specialists, is the first to analyze the eroticism of the esoteric without sensationalism or cheap generalizations, but on the basis of expert scholarship and attention to textual and historical detail. While there are few other domains where the imagination may so easily run wild, the various contributions seek to distinguish fact from fiction--only to find that historical realities are sometimes even stranger than the fantasies. In doing so, they reveal the outlines of a largely unknown history spanning more than twenty centuries.